Convective heat transfer of high temperature molten salt flowing across tube bundles of steam generator in a solar thermal plant. (August 2018) - Yao, Fan; Bi, Qincheng; Dong, Xinyu
Highlights: A novel convective heat transfer experimental system of molten salt is designed and established. The Nusselt number of high temperature molten salt flowing across tube bundles is studied. The effects of the pressure, temperature and flux on the Nusselt number are analyzed in the shell-and-tube heat exchanger. Several modified heat transfer correlations of molten salt in shell-and-tube heat exchanger are fitted. Abstract: A high temperature molten salt heat transfer experimental system was established and operated over 1500 h, started up and shut down every day, for research and development of steam generator in a solar thermal plant. Convective heat transfer performances of high temperature molten salt was investigated experimentally when it flowed across tube bundles in a shell-and-tube heat exchanger with Reynolds number ranging from 2129 to 10072 and fluid temperature 400–500 °C. Various experiments were respectively carried out to study the effect of pressure (water range: 14–18 MPa), temperature, flux (water range: 200–400 kg h −1 ) and phases of the tube side of heat exchanger. The results show that the Nusselt number of molten salt increases when the flux of water and the temperature of molten salt increased respectively with other conditions unchanged. Moreover, the Nusselt number of molten salt slightly decreases when the pressure of water increased. Finally, based on the experimental data and Zhukauskas correlation, several modified Zhukauskas correlations were proposed, and a good agreement was observed with deviations less than ±16% between the experimental data of molten salt and the empirical correlation.